MENINGKATKAN KEMAMPUAN MENULIS KATA DIFGRAF MELALUI METODE MULTISENSORI PADA ANAK DISGRAPHIA (Single Subject Research di kelas III/B SDN 20 Padang) - Rio Hendri Dinata (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstract:This research is motivated by problems in a child's learning difficulties third class in SDN 20Kalumbuk who have difficulty in writingdisgraphs sayso that even if the child is in third class he was not able to write well. Under theseconditions, the researchers want to prove that the use of Multisensory methods can boost children's writing skills in third grade learning difficultiesin SDN 20Kalumbuk. This study uses a Single Subject Research approach, with desian A –B – A and data analysis techniques using visual analysis chart.fungtions this study indicate that multisensory methods is able to improve thewriting skills of learning difficulties for children third class at SDN 20 Kalumbuk PadangKata Kuci :Disgraphia , Kemampuan , Menulis kata difgraf , Multisensori